ANALISIS MISKONSEPSI SISWA PADA MATERI KONSEP REDOKS MENGGUNAKAN CERTAINTY OF RESPONSE INDEX (CRI) DI SMA NEGERI 9 KOTA BENGKULU - Endah Yuniarti; Amrul Bahar; Elvinawati Elvinawati (ALOTROP, 2020)
This research aimed to describe the student misconceptions and find out the cause of misconceptions on Redox Reaction lesson at the tenth grade of Senior High School 9 Bengkulu in 2018/2019 Academic Year. Research conduct on April 15th until May 24th, 2019. The design of this research is descriptive method. The samples were taken through simple random sampling technique are 67 students of tenth grade MIPA SMA N 9 Kota Bengkulu so that 30 students were sampled. Essay test by Certainty of Response Index (CRI) and interview were used as the instruments of this research. Based on the analysis of research data shows there are misconceptions students. The analysis results show that misconceptions occurred at all sub concept on redox concept so the percentage of misconceptions that occur amounted to 35,7% in the overall student. The results showed the highest percentage of misconceptions in the amount of 46% at sub concept to determine reduction oxidation based on oxidation number on molecules and ion. The lowest percentage of misconceptions in the amount of 23% at indicator to in the sub concept of understanding oxidation and reduction in a redox reaction in terms of changes in oxidation number. Based on the results of interviews, causes of student misconception are derived from internal and external factors. Internal factors are derived from students such as students' associative thinking, student apperception and wrong intuition, students' abilities are lacking, low of students' motivation and learning interests during the learning process, students' learning methods, and students' selfconfidence in CRI values and external factors such as methods learning and limited learning resources.